2015
DOI: 10.3390/jof1030397
|View full text |Cite
|
Sign up to set email alerts
|

Masking the Pathogen: Evolutionary Strategies of Fungi and Their Bacterial Counterparts

Abstract: Pathogens reduce immune recognition of their cell surfaces using a variety of inert structural polysaccharides. For example, capsular polysaccharides play critical roles in microbial survival strategies. Capsules are widely distributed among bacterial species, but relatively rare in eukaryotic microorganisms, where they have evolved considerable complexity in structure and regulation and are exemplified by that of the HIV/AIDS-related fungus Cryptococcus neoformans. Endemic fungi that affect normal hosts such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 165 publications
1
5
0
Order By: Relevance
“…Possibly as a result of the capsule mutant being rapidly cleared, the alveolar macrophage population was not overwhelmed. The capsule in other species is known to potentially mask the pathogen [ 35 ], and we also observed that with A. baumannii . Given all our data, it is most likely that the enhanced susceptibility to killing and phagocytosis by capsule deficiency leads to more rapid digestion and release of TLR ligands that leads to this increased innate immune response.…”
Section: Discussionsupporting
confidence: 75%
“…Possibly as a result of the capsule mutant being rapidly cleared, the alveolar macrophage population was not overwhelmed. The capsule in other species is known to potentially mask the pathogen [ 35 ], and we also observed that with A. baumannii . Given all our data, it is most likely that the enhanced susceptibility to killing and phagocytosis by capsule deficiency leads to more rapid digestion and release of TLR ligands that leads to this increased innate immune response.…”
Section: Discussionsupporting
confidence: 75%
“…We observed antibody VRC34.01 to have few epitope segments, low epitope-glycan content, and high epitope-conformational variability. Few epitope segments enable easy creation of epitope mimics; low epitope-glycan content reduces barriers to immune recognition (glycan masking is a strategy used broadly by pathogens (Park and Williamson, 2015)); and high epitope-conformational variability permits epitope recognition in multiple structural contexts (Tainer et al, 1984). Thus, despite VRC34-class antibodies only being identified in a single donor and only with 50% breadth, its characteristics suggest that vaccine design based on the epitope of antibody VRC34.01 could be especially promising.…”
Section: Resultsmentioning
confidence: 99%
“…The yeast must derive energy for cellular processes as well as obtain space to accommodate its expanding population. During the competition, yeast cells often experience nutrient and water limitation [113]. The latter may cause yeast cells to become desiccated.…”
Section: Tolerance To the Limitation Of Nutrients And Watermentioning
confidence: 99%